Effect and fate study with blue mussels and microplastic in a laboratory experiment: feces depuration - Aurelia Laubscher; Thea Hamm; Mark Lenz (PANGAEA, 2021)
Adult blue mussels (Mytilus spp.) were exposed to microplastic particles in a controlled laboratory experiment. Feces was collected after the exposure phase of 2 hours and after 24 and 48 hours of depuration in filtered sea water and the amount of PS beads was determined.
In: Laubscher, A et al. (2021): Effect and fate study with blue mussels and microplastic in a laboratory experiment [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.937475